PENGARUH MOTIVASI INTRINSIK DAN KOMPETENSI TERHADAP PRODUKTIVITAS KARYAWAN BAGIAN MOVEMENTSPEED PADA PERUSAHAAN OTOMOTIF PT. INDONESIA NIPPON SEIKI - Muhammad Verry; Haidilia Maharani (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. The purpose of this research is to determine the influence of intrinsic motivation and competence on employee productivity in the movementspeed division of an automotive company, PT Indonesia Nippon Seiki. The research employs a quantitive method with a saturated sampling technique involving 57 respondents. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination, and hypothesis testing. The results indicate that intrinsic motivation has a significant effect on employee productivity, with a coefficient of determination of 37.2%, and the hypothesis test shows that t-value > t-table (5.708 > 2.004). Competence also has a significant effect on employee productivity, with a coefficient of determination of 18.4%, and the hypothesis test shows that t-value > t-table (3.438 > 2.004). Simultaneously, intrinsic motivation and competence significantly affect employee productivity, as shown by the regression equation Y = 10.343 + 0.557X1 + 0.151X2. The coefficient of determination is 39.4%, indicating that the remaining 60.2% is influenced by other factors. The hypothesis test also shows that F-value > F-table (17.838 > 3.17). Keywords: Intrinsic Motivation, Competence and Employee Productivity.